2016
DOI: 10.1016/j.celrep.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

CENP-A Ubiquitylation Is Inherited through Dimerization between Cell Divisions

Abstract: SUMMARY The presence of chromatin containing the histone H3 variant CENP-A dictates the location of the centromere in a DNA sequence–independent manner. But the mechanism by which centromere inheritance occurs is largely unknown. We previously reported that CENP-A K124 ubiquitylation, mediated by CUL4A-RBX1-COPS8 E3 ligase activity, is required for CENP-A deposition at the centromere. Here we show that pre-existing ubiquitylated CENP-A is necessary for recruitment of newly synthesized CENP-A to the centromere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 56 publications
4
28
2
Order By: Relevance
“…A complete turnover of all preexisting CENP-A molecules has been only previously observed in holocentric organisms (Gassmann et al, 2012). Our findings further demonstrate that post-translational modifications on preexisting centromeric CENP-A are not essential to guide new CENP-A deposition at the centromere in contrast to previously described models (Niikura et al, 2015(Niikura et al, , 2016.…”
Section: Discussionsupporting
confidence: 58%
“…A complete turnover of all preexisting CENP-A molecules has been only previously observed in holocentric organisms (Gassmann et al, 2012). Our findings further demonstrate that post-translational modifications on preexisting centromeric CENP-A are not essential to guide new CENP-A deposition at the centromere in contrast to previously described models (Niikura et al, 2015(Niikura et al, , 2016.…”
Section: Discussionsupporting
confidence: 58%
“…Whereas molecular steps allowing eviction of overloaded pool of CENP-A are largely unknown, there are reports of stabilization of nascent CENP-A occurring in G1 (Lagana et al, 2010;Liu and Mao, 2016;Perpelescu et al, 2009), suggesting that addition of CENP-A ´´stabilization´´ mark would happen prior to DNA synthesis. A recent addition to this theme is the report of ubiquitylation of parental CENP-A as a requirement to recruit nascent CENP-A (Niikura et al, 2016). Centromeric CENP-A levels could also be normalized during S phase passage, in which the mix of parental and G1-loaded pools of CENP-A would be coordinately and preferentially segregated to the granddaughter centromere which inherited a decreased number of CENP-A molecules from the previous generation.…”
Section: Possible Mechanisms To Maintain Homeostasis Of Cenp-a Levelsmentioning
confidence: 99%
“…Of these, only three have been reported within the histone fold domain [2023]. Using epitope-tagged CENP-A, studies have identified phosphorylation of S68 within loop 1 [23], and ubiquitination of K124 near the pseudo-dyad of the nucleosome [21, 22]. We previously analyzed chromatin-bound native CENP-A (nCENP-A) and identified acetylation of K124 (K124ac), which was enriched at G1/S phase [20].…”
Section: Introductionmentioning
confidence: 99%